ARRANGEMENT OF THE BAJO ETHNIC FISHERMEN SETTLEMENT AREA BASED ON ECOLOGY AND LOCAL WISDOM ON THE COAST OF BONE BAY - Dr. BUDIMAWAN; W. ASWITA; M. LAMPE; H. NAPING; MB. SELAMAT; A. A. ARIEF (International Journal of Multidisciplinary Research and Studies, 2022)
Existence edge sea or coast beach is a relative space dominant for settlement waters in Indonesia. of all many settlement glasses of water in Indonesia, one of them is the area that lives in the Bajo Tribe, which is located in the Bajo Village, District Tanete East Riattang, Bone Regency. Forming process settlement the Bajo Tribe on the Coast Bonne Bay to moment this, no free from condition geography and environment nature background behind by activity daily inhabitant as fisherman or sailor. Change pattern settlement from the sea ( bido ') to land, causing the Bajo Tribe to experience change. This thing occurs because ecological, there is a different condition for life on land than life in the sea. Temporary from side settlement seen that part big condition house stay from the Bajo Tribe Community in a category no worthy inhabit and tend slum. Impact negatively from existence settlement slum this not only character experienced micro directly by the settlers but could character meso nor macro which is also felt by the people around settlement slum that. Problem settlement slum this will could lower quality environment coast and coast, as well as more far could damage ecosystem the sea that will have an impact on reducing results fish catch. Because that, research this aim to Describe characteristics settlement Fishermen of the Bajo Nation on the Coast Bone Bay and Instruct the right concept in residential area arrangement Bajo - based fishermen ecology and wisdom local. Research Type this is type of non-experimental and non-experimental research descriptive-qualitative. Study this using the Snowball Sampling Technique and using SWOT analysis. Results: Based on the Result of Analysis and Observation directly on-location research, can be known that there are 3 types of pattern settlements in the Bajo Tribe Settlement Area on the Coast Bone Bay namely 1) pattern settlement longitudinal (linear), 2) pattern settlement group, and 3) pattern settlement spread out. Based on the results evaluation influence pattern settlement with aspect continuity could conclude that configuration most suitable room with draft sustainable for the arrangement of the Bajo ethnic settlement area, namely: pattern settlement group that can minimize damage to the environment. Other than that can also be used as a place for effort to increase the economy Public as well as could maintain values and social culture Public coast.